Consumer and sensory evaluation techniques : how to sense successful products - Saint-Denis, Cecilia Y. (Wiley, 2018)
This unique manual describes how to implement specific sensory and consumer methods based on context and objective. Presented in a direct and straightforward language that will speak to the industry professionals and academics who are on the ground attempting to solve technical questions, it reviews, step by step, the various stages of a product evaluation. Included are practical examples from many industries that practitioners can relate to. The book also shows how to build a sustainable short-, medium-, and long-term product evaluation strategy, and guides readers on how to create customized methods, or even completely new approaches.